The function and regulation of PD-L1 in immunotherapy - Libin Guo; Yao Lin; Hang Fai Kwok (International Association of Physical Chemists (IAPC), 2017)
PD-L1, also known as B7-H1, is a type I transmembrane protein, which is expressed in different kinds of tumor cells. It is correlated with poor clinical outcome of patients with various types of tumors. PD-L1 can regulate tumor microenvironment or tumor related immune response through suppressing T cell or NK cell mediated immune response. PD-L1 expression is regulated by various cytokines, such as LPS, GM-CSF, IL-4, TGF-β, TNF-α. PD-1 and PD-L1 are the members of B7 and CD28 superfamily, respectively. The B7/CD28 interaction plays a central role in immune tolerance. PD-L1 can bind to PD-1, which leads to the suppression of lymphocyte activation and apoptosis of lymphocytes. Anti-PD-L1 therapy is one of the immunotherapies to treat cancer (especially solid tumor). PD-L1 expression may be associated with efficacy of anti PD-1/PD-L1 therapy. In this review, we will focus on the regulation mechanism of PD-L1 expression, and describe the role of PD-1/PD-L1 binding on the anti-PD-1/PD-L1 therapy.